Digital therapeutics and mHealth applications in cardiovascular prevention: strongest evidence in hypertension and emerging perspectives in dyslipidemia - Arkadiusz Wysocki; Małgorzata Wierzowiecka; Arkadiusz Niklas (Frontiers in Digital Health, 2026)
Digital health interventions are increasingly used to support cardiovascular prevention, but their clinical maturity differs across risk factors and types of technology. This narrative review summarizes current evidence and implementation challenges related to digital therapeutics, mobile health applications, telemonitoring systems, and integrated digital health platforms in hypertension, dyslipidemia, and broader cardiometabolic prevention. The strongest evidence currently supports digitally enabled blood pressure management, particularly when home blood pressure monitoring, telemonitoring, behavioral support, medication adherence tools, and clinician-guided treatment adjustment are integrated into routine care. In contrast, digital interventions for dyslipidemia remain less established and are mainly focused on education, lifestyle modification, adherence support, shared decision-making, and long-term risk reduction. Therefore, most lipid-related digital tools should currently be interpreted as supportive mHealth or prevention interventions rather than fully established digital therapeutics. Successful implementation requires more than patient-facing applications. It depends on clinical workflow integration, professional responsibility for data review and telemonitoring alerts, regulatory and reimbursement pathways, data protection, interoperability, equity, and evidence of clinical and economic value. Future studies should distinguish between digital therapeutics, mHealth tools, telemonitoring systems, and digital ecosystems, and should evaluate clinically meaningful endpoints, safety, cost-effectiveness, and long-term sustainability.